(untitled) (MAUSAM, 2016)
An attempt has been made to study dynamics of consecutive weak/strong spell of north east monsoon for the years, 2009 and 2010 from an energetics aspect. For that different energy terms, their generation and conversion among different energy terms have been computed for consecutive weak and strong phases during Oct to Dec of the above two years over a limited region between 70 °E to 85 °E, 5 °N to 20 °N. These computations are based on daily NCEP 2.5° × 2.5° data for the same period. The transition from weak phase to strong phase of north east monsoon (NEM) observed to be associated with an enhancement in conversion of zonal available potential energy (Az) to zonal kinetic energy (Kz), implying a strengthening of Hadley circulation, favouring the above transition. It is also observed that the transition from weak phase to strong phase is associated with enhanced Baroclinic energy conversion